Two-dimensional dysprosium-modified bamboo-slip-like lithium titanate with high-rate capability and long cycle life for lithium-ion batteries. Issue 45 (7th November 2016) - Cai, Yanjun; Huang, Yudai; Jia, Wei; Zhang, Yue; Wang, Xingchao; Guo, Yong; Jia, Dianzeng; Pang, Weikong; Guo, Zaiping; Wang, Lishi
Abstract : Two-dimensional dysprosium-modified bamboo-slip-like Li4 Ti5 O12 have been synthesized by one-pot hydrothermal method. The samples exhibit superior high-rate capability, and excellent cycle performance. Abstract : Two-dimensional dysprosium-modified bamboo-slip-like Li4 Ti5 O12 (2D Dy-B-LTO) has been synthesized by a one-pot hydrothermal method. The structure and morphology of the as-prepared materials were analyzed by X-ray diffraction (XRD) and electron microscopy. The results show that dysprosium is doped into both 8a and 16d sites of Li4 Ti5 O12, which is determined by Rietveld analysis of XRD data. Dysprosium-modified Li4 Ti5 O12 shows bamboo-slip-like nanosheet morphology and the possible formation mechanism is proposed. The as-prepared samples exhibit superior high-rate capability and excellent cycle performance. The initial discharge capacity of Li4− x /3 Ti5−2 x /3 Dy x O12 ( x = 0.02) is 181.8 mA h g −1 at 20C; surprisingly, even when cycled at 100C, the discharge capacity still retains 140.9 mA h g −1 after 1000 cycles. The improved electrochemical performance could be attributed to bamboo-slip-like nanosheets in conjunction with dysprosium doping, which can offer more ion and electron transporting channels and increase the amount of Ti 3+ /Ti 4+ mixing as charge compensation.